WORK PRODUCTIVITY FROM THE PERSPECTIVE OF ISLAMIC ECONOMIC PHILOSOPHY - Hasanah, Uswah; Yafiz, Muhammad (Journal of Sharia Economics, 2026)
This study aims to examine the philosophical implications of work productivity in human life, which is closely related to time management, responsibility, and the quality of good deeds. This study uses a qualitative approach with library research. This approach was chosen because the research focuses on conceptual and philosophical studies of work productivity from an Islamic perspective. The results show that work productivity is not only understood as the ability to produce maximum output, but also as a form of devotion to Allah SWT. Islam views work as worship when it is based on sincere intentions, carried out in a legal manner, and aims to benefit oneself and society. Islamic philosophical values such as monotheism, trustworthiness, ihsan, and justice are the main foundations for building a productive and sustainable work ethic. The concept of work in Islam emphasizes a balance between material and spiritual aspects, so that productivity is not solely measured by economic results but also by the moral values and blessings generated. Thus, Islamic philosophy offers a paradigm of work productivity that is holistic, humanistic, and oriented towards happiness in this world and the hereafter.